Algorithms weighing lives and freedoms: The case of China’s health code - Ina Virtosu; Chen Li (Smart Cities and Regional Development Journal)
In response to the COVID-19 outbreak in the beginning of 2020, Chinese local governments created a software extension on existing mobile applications to monitor citizens’ movement and collect their health data. Very quickly China’s health code became a key resource for the country’s governments to track and contain COVID-19 cases using time, location, and personal interactions. China’s health code system represents an unprecedented form of “biological” governance, which demonstrates and supports the transformation empowered by digital technologies, enhancing the access to healthcare and fusing together mass surveillance and fundamental public service provision. Digital contact tracing has attracted enormous interest among academics and legislators since the outbreak of COVID-19, which resulted in several policy papers and research works, discussing issues, such as the effectiveness and accuracy of virus detection, as well concerns in regard to discrimination and data privacy. However, most of the articles refers to technologies and its implications in the West, and less to the peculiarities and problems related to the use of Chinese health code. Present research analysis the issues related to difficulties to achieve a balance between China’s “zero-COVID policy” and freedom of movement, as well those regarding multiple health code’s proliferation, health code abuses and misuses by officials who do not want to miss any cases for fear of outbreak or being fired. Since China’s health code system is still far from being centralized and uniform across the country, the mutual recognition system has resulted in considerable problems for those who find themselves in high-risk areas.